Ventrolateral prefrontal cortex is required for performance of a strategy implementation task but not reinforcer devaluation effects in rhesus monkeys. - Baxter, MG; Gaffan, D; Kyriazis, D; Mitchell, A (2009)
The ability to apply behavioral strategies to obtain rewards efficiently and make choices based on changes in the value of rewards is fundamental to the adaptive control of behavior. The extent to which different regions of the prefrontal cortex are required for specific kinds of decisions is not well understood. We tested rhesus monkeys with bilateral ablations of the ventrolateral prefrontal cortex on tasks that required the use of behavioral strategies to optimize the rate with which rewards were accumulated, or to modify choice behavior in response to changes in the value of particular rewards. Monkeys with ventrolateral prefrontal lesions were impaired in performing the strategy-based task, but not on value-based decision-making. In contrast, orbital prefrontal ablations produced the opposite impairments in the same tasks. These findings support the conclusion that independent neural systems within the prefrontal cortex are necessary for control of choice behavior based on strategies or on stimulus value.